Identificação dos elementos de governança para a integração entre redes de cooperação regionais - Silva, João Cláudio Saenger (Universidade do Vale do Rio dos Sinos, 2013)
This study originated from the perception of opportunity in linking existing cooperation networks of small and medium sized companies in Brazil. In recent research the number of networks operating in the country comes close to 800. The study based on this occasion sought to analyze which elements of governance exist in relationship networks and what characteristics these elements must have for interconnection between network reach the best possible result. To this came up with ten of governance that were initially examined through the theoretical ones. The method used for this study was the design research. The ten identified governance elements are, trust, consensus goals, number of companies, number of networks, centralization, formalization, specialization, incentives, coordination, and control. Interviews were conducted with experts and potential users. As a result of this study we propose a final framework, with each element and it’s characteristic.
Keywords: Redes de cooperação; Governança de redes; ACCNPQ::Ciências Sociais Aplicadas::Administração